Situating Held v. Montana in the Youth Climate Litigation Movement - Daniel Ziebarth (University of Vienna Law Review, 2024)
The pace of global climate change has been accelerating. Simultaneously, the number of climate-based litigation brought to courts has been increasing. Among this rise in climate-based litigation are cases in which petitioners are young people advancing youth-based claims of rights violations relating to climate change. Scholars have begun to take note of this trend, and early research has emerged on youth-led climate litigation. In the United States, a recent landmark decision occurred in the case of Held v. Montana. The outcome of this case was novel in the United States context, as the youth plaintiffs received a favourable decision from the Montana trial court, which found that the defendants, which were state agencies and associated individuals, had tangibly harmed the youth plaintiffs through their contributions to fossil fuel activities. In this article, I situate the novel outcome of this case in relation to the existing literature and previous cases with similar claims. Importantly, I suggest how lawyers and scholars should increasingly focus on the influence of sub-national courts and constitutional clauses in shaping the trajectory of youth-led, rights-based climate litigation.